2018
DOI: 10.1097/aln.0000000000001927
|View full text |Cite|
|
Sign up to set email alerts
|

No Differences in Renal Function between Balanced 6% Hydroxyethyl Starch (130/0.4) and 5% Albumin for Volume Replacement Therapy in Patients Undergoing Cystectomy

Abstract: Background The use of artificial colloids has declined in critical care, whereas they are still used in perioperative medicine. Little is known about the nephrotoxic potential in noncritically ill patients during routine surgery. The objective of this trial was to evaluate the influences of albumin 5% and balanced hydroxyethyl starch 6% (130/0.4) on renal function and kidney injury. Methods One hundred urologic patients under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 41 publications
1
24
0
3
Order By: Relevance
“…Also, in two randomized controlled trials [19,33] and a retrospective cohort study [20] of children undergoing cardiac surgery, HES 130/0.4 was associated with less fluid balance and lower amounts of transfusion than albumin and was not negatively associated with postoperative outcomes, including renal morbidity. A randomized controlled trial in patients undergoing cystectomy found that perioperative changes in cystatin C as a component of glomerular filtration rate and neutrophil gelatinase-associated lipocalin as a marker of tubular injury did not differ between balanced HES 130/0.4 (Volulyte ® ; Fresenius Kabi GmbH, Germany) and albumin [21]. All of the literature above support the use of 6% HES 130/0.4 as an effective and safe alternative to albumin during surgery.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Also, in two randomized controlled trials [19,33] and a retrospective cohort study [20] of children undergoing cardiac surgery, HES 130/0.4 was associated with less fluid balance and lower amounts of transfusion than albumin and was not negatively associated with postoperative outcomes, including renal morbidity. A randomized controlled trial in patients undergoing cystectomy found that perioperative changes in cystatin C as a component of glomerular filtration rate and neutrophil gelatinase-associated lipocalin as a marker of tubular injury did not differ between balanced HES 130/0.4 (Volulyte ® ; Fresenius Kabi GmbH, Germany) and albumin [21]. All of the literature above support the use of 6% HES 130/0.4 as an effective and safe alternative to albumin during surgery.…”
Section: Discussionmentioning
confidence: 95%
“…The sample size was the total number of eligible patients seen during the 3-year study period; no a priori sample size calculation was performed because the study was retrospective. In recent literature, the postoperative incidence of AKI [16,21]. We assumed, therefore, that a 10% difference in the primary outcome would be clinically relevant and calculated that 540 matched patients (270 pairs) were needed to have 80% power to detect a 10% absolute difference in the incidence of AKI between the HES and the albumin group at the 0.05 level.…”
Section: Associations Between Hes or Albumin And Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…One small single-center, single-blinded randomized trial compared 5% albumin solution to 6% HES 130/0.4 solution used as part of a GDFT protocol in patients undergoing elective cystectomy [73]. There was no significant difference between the two groups with respect to the primary outcome, i.e., kidney function and kidney injury assessed up to postoperative day 90.…”
Section: Yesmentioning
confidence: 99%
“…Demir et al [20] compared HES 130/0.4 (Voluven) to 4% gelatin (Gelofusine) in patients who underwent a liver transplant and reported a nonsignificant incidence of acute kidney injury (AKI) grade I in the gelatin group (2 vs. 5). Two studies [26,38] compared HES 130/0.4 (Voluven) to 5% human albumin and reported no differences in the renal dysfunction at neither immediate postoperation [36,38] nor 3-month postoperation [38] using the cystatin C/Cr ratio. Critical Care Research and Practice [28,37,39], Plasmalyte [29,54], and acetate buffer crystal [40]) in kidney transplant patients.…”
Section: Renal Function (Colloid Vs Colloid/crystalloid)mentioning
confidence: 99%